Exploring the role of healthcare providers in supporting women after pregnancy loss: A scoping review - Rosyidah, Rafhani; Azizah, Nurul; Jayanti, Ratna Dwi; Prisusanti, Retno Dewi (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS The study examines healthcare providers’ roles in delivering holistic physical, emotional, and psychosocial support to women after pregnancy loss. The findings identify major provider barriers—limited training, institutional constraints, and emotional burden—and recommend improved training, clearer guidelines, and stronger support systems.   ABSTRACT Objective: Pregnancy loss is a complex emotional experience with a significant impact on women's physical and psychosocial health. This study aimed to explore the role of health workers in supporting women after pregnancy loss, focusing on their physical, emotional, and psychosocial needs, as well as the barriers faced by health workers. Materials and Methods: A systematic search was conducted on six electronic databases, namely PubMed, Science Direct, Springer, ProQuest, Sage Journals, and EBSCOhost, using keywords related to pregnancy support, pregnancy loss, and challenges faced by health workers. Articles published within the last 10 years (2014-2024) were selected for this review. The selection process followed PRISMA guidelines, starting with the identification of 383 articles, followed by the removal of duplicates and screening of titles and abstracts. After the eligibility assessment stage, five articles were selected that met the inclusion criteria. Data were systematically extracted using tables that included study purpose, design, participants, type of pregnancy loss, and key findings. The results of the analysis mapped the physical, emotional, and psychosocial support provided by health workers and the barriers affecting the quality of that support. Results: Integrating physical, emotional, and psychosocial care is crucial to improve outcomes for women experiencing pregnancy loss. Addressing challenges faced by healthcare providers will enhance service quality and patient support. Conclusions: Holistic support that includes physical, emotional and psychosocial aspects is essential in helping women to cope with pregnancy loss. However, barriers such as lack of training and institutional support affect the effectiveness of care. This review recommends strengthening formal training, developing structured guidelines, and improving support systems for health workers to enhance the quality of care and professional well-being.